An Analysis of Errors Caused by Omani EFL Learners in Pronouncing Certain Consonant Sounds - Mohammed Alyaqoobi, Zainab; Fatimah, Ali; Norrihan, Sulan (Universiti Malaysia Pahang, 2016)
Omani EFL learners face various problems in learning different skills such as reading, writing, grammar, vocabulary and pronunciation. In particular, it is very difficult for Omani EFL learners to pronounce certain consonant sounds correctly. For instance, the sound /p/ of the English language do not have similar sound in the phonemic system of the Arabic language, so it is not easily recognised by Omani students. This sound is always replaced by /b/, a sound in the Arabic phonemic system. Similar case is observed with the sound /ʧ/, /v/ and /g/, which do not have similar sounds in the Arabic consonantal system. Consequently, these are often replaced by the sound /ʃ/, /f/ and /ʤ/ respectively. The absence of one sound of a language phonemic system from another phonemic system of another language creates problem to learners. Hence, the purpose of this study is to examine the difficulties experienced by Omani EFL learners in pronouncing certain English consonant sounds. The study also provides a theoretical description of first language interference which affects Omani ESL learners’ pronunciation of /p/ and /ʧ/ consonant sounds in words in isolation for three positions – initial, middle and final. Quantitative research methodology was employed, with the use of a diagnostic test to assess students’ pronunciation on certain consonant sounds. A questionnaire was also utilized to gather information from the teachers pertaining to students’ difficulties in pronouncing certain consonant sounds. The study is significant as it offers a practical outcome where teachers will be able to use suitable pedagogical approaches in handling this problem in Omani EFL classes.